Methylation-Demethylation Dynamics: Implications of Changes in Acute Kidney Injury - Anubhav Chakraborty; Pragasam Viswanathan (Analytical Cellular Pathology)
Over the years, the epigenetic landscape has grown increasingly complex. Until recently, methylation of DNA and histones was considered one of the most important epigenetic modifications. However, with the discovery of enzymes involved in the demethylation process, several exciting prospects have emerged that focus on the dynamic regulation of methylation and its crucial role in development and disease. An interplay of the methylation-demethylation machinery controls the process of gene expression. Since acute kidney injury (AKI), a major risk factor for chronic kidney disease and death, is characterised by aberrant expression of genes, understanding the dynamics of methylation and demethylation will provide new insights into the intricacies of the disease. Research on epigenetics in AKI has only made its mark in the recent years but has provided compelling evidence that implicates the involvement of methylation and demethylation changes in its pathophysiology. In this review, we explore the role of methylation and demethylation machinery in cellular epigenetic control and further discuss the contribution of methylomic changes and histone modifications to the pathophysiology of AKI.